Description of Hylopanchax paucisquamatus (Cyprinodontiformes: Poeciliidae), a new lampeye species from the Odzala-Kokoua National Park, Republic of Congo - Sonnenberg, Rainer; Friel, John P.; van Der Zee, Jouke R. (Zootaxa, 2014)
A new deep-bodied Hylopanchax species is described from the northwestern Congo basin. Hylopanchax paucisquamatus, new species, was collected in the Odzala-Kokoua National Park in the Likouala River drainage of the Republic of Congo. It differs from its congeners, including the deep-bodied H. leki and H. ndeko, by a unique combination of morphological characters, including low number of mid-longitudinal and transverse scales, number of dorsal-fin rays, and position of dorsal-fin origin in relation to anal-fin. It is the only deep-bodied species currently known outside the Kasaï River drainage.